DEVELOPMENT OF LEARNING MEDIA FOR MOTORCYCLE ELECTRONIC FUEL INJECTION SYSTEM BASED ON FLIP HTML5 AT THE DEPARTMENT OF MOTORCYCLE ENGINEERINGAT SMK SUMBER DAYA BEKASI - Sugiarto; C Rudy Prihantoro; Ratu Amilia Avianti (Universitas Negeri Semarang, 2024)
The development of technology and information is very rapidly growing and influential in the world of education. Technology and information in learning are very helpful for educators in utilizing technology facilities to prepare for the learning process or when the learning process takes place. This study aims to develop Flip Html5-based e-book learning media for motorcycle Electronic Fuel Injection system material. This research uses the Research and Development (R&D) method using the 4D development model in its development, which must go through an expert assessment as a successful process of testing the feasibility of the developed product before it is later tested and used. The results of the feasibility test of Flip Html5-based e-book learning media get a percentage of 96.36% from material expert validators, 94.54% from media expert validators, and 89.23% from the results of the media feasibility test of 35 students. So, the results that have been carried out can be concluded that the Flip Html5-based e-book learning media for Motorcycle Electronic Fuel Injection system material developed in this study are